Risk Sharing and the Dynamics of Inequality - Ezra Friedman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
Risk averse agents who engage in risky production activities frequently participate in some sort of arrangement to share risk. When there are issues of moral hazard, optimal risk sharing typically involves spreading risk over time as well as over space. Agents who suffer bad outcomes can spread risk over time by borrowing against future earnings to supplement present consumption. In this paper I analyze the effect that such intertemporal risk sharing has on the distribution of consumption and utility. I find that in most cases intertemporal risk sharing leads to a spreading of the utility weight distribution. Under the optimal contract agents who suffer negative shocks respond by working harder and bearing more risk, exposing them to the likelihood of more negative shocks.
Keywords: 330